Adlay, an ancient functional plant with nutritional quality, improves human health - Weng, Wen F.; Peng, Yan; Pan, Xin; Yan, Jun; Li, Xiang D.; Liao, Zhi Y.; Cheng, Jian P.; Gao, An J.; Yao, Xin; Ruan, Jing J.; Zhou, Mei L. (Frontiers in Nutrition, 2022)
Adlay (Coix lacryma-jobi L.), a crop closed related to main (Zea mays L.) and sorghum (Sorghum bicolor L.), originated in tropical/subtropical regions of Asia and Africa; southwest China is one of the primary centers of this plant’s origin, evolution and migration. Adlay is a traditional high-value minor crop for both medicinal and food uses. Adlay has anti-tumor, anti-bacterial, anti-inflammatory, analgesic, blood sugar and blood lipid-lowering effects, and has high comprehensive application value. In order to clarify the main bioactive components and phytochemical compounds, and fully explore its utilization value, this review summarizes the research to date the main functional ingredients of the adlay and the exploration their utilization value, including amino acids and proteins, oils, vitamins and minerals, polysaccharides, polyphenols and others. This study also highlights the application of genome sequencing for tailoring a nutrient rich adlay cultivar and nutraceutical product development. In addition, acquisition of high-density genomics data combined with the next-generation phenotypic analysis will undoubtedly improve our understanding of potential genetic regulation of adlay nutraceutical traits. This review not only provides new insights and ideas for the research of adlay in comparison and evolutionary genomics, but also provides a very favorable reference for molecular breeding and genetic improvement of this small important crop.